Parent Involvement in Shapping Behavior of Elementary School Children - Sri Handayani; Nur Wulan Agustina; Istianna Nurhidayati (Indonesian Journal of Global Health Research, 2021)
School-age children will basically spend a lot of time in school. This condition will have great potential to buy street food sold in the school environment. Parents in this case are mothers who have an important role in directing children's snacking behavior. Objective: This study aims to analyze the involvement of parents in shaping basic child snacking behavior. This research is a quantitative study using an analytical survey method with a cross sectional approach. The sample size of the study was 74 children, which were taken using a simple random sampling technique. Collecting data using a questionnaire to measure children's snacking behavior and parental involvement. Data analysis used multiple logistic regression with a significance level of 95%. The results showed that there was a relationship between the variables of breakfast habituation, giving pocket money and family habits of snacking outside, which were closely related to children's snacking behavior at school. There is one variable, namely bringing lunch to school is not related to children's snacking behavior. Based on the results of the study, it can be concluded that parental involvement in the formation of snacking behavior is the habit of preparing breakfast, giving pocket money, and family eating habits.